Formulasi Granul Effervescent Ekstrak Aseton Rimpang Kencur (Kaempferia Galanga L.) dengan Variasi Konsentrasi Polivinilpirolidon - Nurul Afifi Lobubun; Lutfi Chabib (Journal of Pharmaceutical and Health Research, 2022)
Kencur is one of the plants that is useful as an anthelmintic drug. This study aims to formulate effervescent granules of acetone extract of Kencur rhizome (Kaempferia galanga L.) with various concentrations of polyvinylpyrrolidone. Kencur rhizome extraction was carried out by maceration method using acetone solvent for 3 days then filtered and concentrated with a rotary vacuum evaporator. The extract was granulated using the wet granulation method with a ratio of citric acid monohydrate and tartaric acid 1:2. Variations in PVP concentrations were 2%, 4%, and 6%. Physical evaluation of granules includes Density and Porosity, Compressibility Index (Carr Index), Flow Time, and Angle of Bed. The best porosity was in formula 3 with 30.47±1.471. The compressibility index (Carr Index) of the three formulas is in the range of 515%. The best dosage flow times were formulas 2 and 3 with 8.67±0.526 and 7.58±0.344. The Hausner Ratio of the three formulas is below 1.25. The angles of repose in formulas 1 and 2 are 24.94º and 29.74º with a recline angle <40. The foam stopping time is 23 seconds. From theresults abtained it can be concluded that the formula with good pharmaceutical properties is formula 3 with a variation of 6% pvp concentration.